Position of Husband and Wife, Gender Relations, and Legal Pluralism in Customary Marriage in Indonesia: A Study of Jujur and Semanda Marriages in Lampung - Ami Rizki Purnawan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study examines the position of husband and wife, gender relations, and the practice of legal pluralism within jujur and semanda customary marriages among the Lampung community. The central problem addressed concerns the unequal social valuation of spouses across these two forms of customary marriage and its implications for gender relations. The study aims to analyze the legal and social positions of husbands and wives in jujur and semanda marriages, as well as community responses to the continued application of these customary practices. This research employs a qualitative method with a sociological approach. The analysis is grounded in social construction theory and gender relations within the framework of legal pluralism. Data were collected through interviews, observation, and documentation among the Lampung Pesisir customary community in Lampung Province. The findings indicate that semanda marriage is maintained to ensure the continuity of the wife’s family lineage and as an economic strategy; however, it remains socially perceived as less prestigious. Individuals with higher educational backgrounds tend to view semanda marriage as socially equivalent, whereas those with lower educational levels often regard it as undermining male status. This study recommends strengthening legal and social literacy to foster more egalitarian spousal relations within the context of legal pluralism.